Evolutionary ontology and biofile transformation of culture - Šmajs, Josef (Civitas: revista de Ciências Sociais, 2019)
The author claims that two large transformations of the human adaptive strategy have occurred in the course of our species’ history: first, the self-preservation modification at the beginning of the anatomically modern humans’ origination; second, the spiritual abandonment of live nature two millennia before the end of the Neolithic culture. Moreover the third transformation, the shift from the predatory spiritual paradigm to the biofile paradigm, has to be undergone today. This transformation is specified with respect to the natural sciences and education system. *** Ontologia evolutiva e transformação biofílica da cultura *** O autor afirma que no curso da história da nossa espécie ocorreram duas grandes transformações na estratégia adaptativa humana: primeiro, a modificação da autopreservação no início da origem anatomicamente moderna dos humanos; segundo, o abandono espiritual da natureza viva dois milênios antes do fim da cultura neolítica. E a terceira transformação, esta a ser efetivada hoje, corresponde à mudança do paradigma espiritual predatório para o paradigma biofílico. Essa transformação é especificamente relativa às ciências naturais e ao sistema educacional. Palavras-chave: Ontologia evolutiva. Natureza. Cultura. Paradigma espiritual predatório. Paradigma espiritual biofílico.